A variação entre ter e haver em construções existenciais na fala e na escrita da variedade riopretense - Oliveira, Carolina Sartori de [UNESP] (2014)
The researches involving existential ter and haver have shown that existential ter is practically categorical in spoken language. However, in written language haver seems to resist and alternate with ter in existential contexts. The general object of this research conducted in apparent time is to verify if, in the spoken language of São José do Rio Preto, the linguistic change between the existential verbs ter and haver is practically consolidated as it was confirmed in other varieties, indicating categorical levels of ter in the spoken language of São José do Rio Preto. Based on such statement, another point that will be verified is if in the written language of children who attend Junior High School occurs a schooling process which promotes the learning of existential haver, classified as a conservative variant. The theory used in this research is based on the assumptions of the Sociolinguistic Variation developed by Weinreich, Labov and Herzog ([1968] 2006), in which these authors define the language as an object of study used in social contexts and as a heterogeneous object, which differs from the concepts of Saussure ([1916] 1977). Based on this conception of language in use this research analyses two corpora, one of spoken language and another of written language, specifically from children attending Junior High School. The analyses of the data were performed by the Goldvarb statistical program, which provides percentages and relative weights of the linguistic and social group of factors selected to interpret this phenomenon in the São José do Rio Preto’s variety. The results revealed that in spoken language the linguistic groups of factors have an influence on the variation process that includes existential ter and haver, which doesn´t occur in written language, because in this modality just the social group of factors was selected as a conductor of the variation between these existential verbs. The interpretation of the ...